Improving Students’ Competence in Writing Descriptive Text by Using Realia Media - Agus Salim Lamusu (Newinera Publisher, 2022)
The goal of the study is to increase students' writing skills in descriptive writings by incorporating realia media into the classroom. The study makes use of action research in the classroom (CAR). In this study, the tool of investigation is the Test and Observation Sheet. The outcome of the investigation. The study discovered that using realia media may help students enhance their writing skills while producing descriptive texts. It is possible to draw the conclusion that there has been an improvement based on the results of the study that was conducted in two cycles (cycle I and cycle II). After being educated via the use of realia media, the student's ability to write descriptive language improves significantly. The use of realia as a medium for improving students' ability to write descriptive texts proved to be quite beneficial. According to the significant result percentage of students score in the pre-test (14 percent), cycle I (43 percent), and cycle II (50 percent), it was supported (81 percent ).